PENGARUH CAFE ATMOSPHERE DAN CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING - Enik Oktafiana; Bayu Kurniawan; Henry Casandra Gultom (CV. Denasya Smart Publisher, 2024)
This study aims to analyze the effect of café atmosphere and customer experience on repurchase intention with customer satisfaction as a mediating variable. Café atmosphere and customer experience are important factors that influence customers' decisions to return. However, previous research results show differences in the relationship between these variables. This study uses a quantitative method with a survey approach. Primary data were collected through questionnaires distributed to Senja customers at Origo Cafe. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of AMOS software. The results showed that café atmosphere did not have a significant effect on customer satisfaction and repurchase intention. Meanwhile, customer experience had a significant effect on customer satisfaction, which ultimately influenced repurchase intention. In addition, customer experience had a significant effect on repurchase intention through customer satisfaction, while café atmosphere did not show this mediating effect. The recommendation of this study is to add other variables to understand the factors that influence customer satisfaction and loyalty. Senja management at Origo Cafe is advised to improve the café atmosphere element and strengthen the customer experience-based marketing strategy through positive interactions and improving product quality.